Spending Spree : the History of American Shopping. - Bix, Cynthia Overbeck (Lerner Publishing Group, 2013)
Ka-ching! Ever stop to think how our modern-day shopping culture came to be? In the early 1800s, stores were few and far between in the United States. General stores supplied everything from fabric and flour to handsaws and clocks. As the country grew, mail-order catalogs arrived at homes across the country, Mom and Pop specialty shops sprang up along Main Street, and later, shopping malls and big box megastores thrived in the suburbs. Then online shopping arrived via the Internet and changed the consumer experience yet again! Buying behaviors also changed over time. For example, did you know.